2001
DOI: 10.1677/joe.0.1710435
|View full text |Cite
|
Sign up to set email alerts
|

Human chorionic gonadotropin (hCG) beta-core fragment is produced by degradation of hCG or free hCG beta in gestational trophoblastic tumors: a possible marker for early detection of persistent postmolar gestational trophoblastic disease

Abstract: The present study was undertaken to investigate whether human chorionic gonadotropin (hCG) -core fragment (hCG cf) was directly produced by gestational trophoblastic tumors. Immunoreactivity of hCG cf was demonstrated in the extracts as well as in the culture media of hydatidiform mole tissues. It was also present in the extracts of choriocarcinoma tissues, and its molar concentration exceeded that of intact hCG. The presence of hCG cf was then confirmed by gel chromatography and Western blot analysis. Immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
(33 reference statements)
2
8
0
2
Order By: Relevance
“…ANC and HCG/β-HCG levels are the sensitive and representative indexes for predicting main toxicities and efficacy; most important, they can be quantitatively evaluated and are superior to other clinical indexes. [23][24][25] Furthermore, after comparing the clinical efficacy and toxicities between 5-FU and FUDR treatments in GTT patients, no obvious differences were found, which is consistent with the in vitro results. 40 Chemotherapeutic efficacy is normally associated with dose intensity, which is defined as the amount of drug delivered per unit of time, regardless of the schedule used.…”
Section: Discussionsupporting
confidence: 77%
“…ANC and HCG/β-HCG levels are the sensitive and representative indexes for predicting main toxicities and efficacy; most important, they can be quantitatively evaluated and are superior to other clinical indexes. [23][24][25] Furthermore, after comparing the clinical efficacy and toxicities between 5-FU and FUDR treatments in GTT patients, no obvious differences were found, which is consistent with the in vitro results. 40 Chemotherapeutic efficacy is normally associated with dose intensity, which is defined as the amount of drug delivered per unit of time, regardless of the schedule used.…”
Section: Discussionsupporting
confidence: 77%
“…The β 6–40 polypeptide chain contains the two hCGβ N -linked carbohydrate moieties, although the oligosaccharides are truncated due to metabolism. Urinary hCGβcf can be isolated with relatively straightforward procedures [15] from a simple urine sample and offers a convenient way of providing insights into glycosylation of the hCGβ subunit and therefore the hCG from which it was derived [18]. This presents an opportunity to indirectly study pregnancy disorders known to exhibit glycoform variants of hCG.…”
Section: Introductionmentioning
confidence: 99%
“…The question whether ITA is a better marker of PTD than hCG+ß parallels the discussion by Okamoto et al (20) regarding the usefulness of hCG ß-core fragment (hCGßcf) for early prediction of subsequent development of post-molar PTD. These authors reported that, due to its short half-life, serum hCGßcf rapidly declined and became undetectable after evacuation of the mole with subsequent spontaneous resolution.…”
Section: Discussionmentioning
confidence: 93%